Aluminum-copper-lithium alloy product with improved properties for underwing elements

By adjusting the chemical composition and process flow of aluminum-copper-lithium alloys and controlling the microstructure of Mn dispersions and δ' precipitates, the problem of reduced fatigue crack propagation resistance of aluminum alloys under variable amplitude loads was solved. This resulted in good yield strength-toughness trade-off performance even after low-temperature aging, making it suitable for aerospace structural components.

CN121548656APending Publication Date: 2026-02-17CONSTELLIUM ISSOIRE
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202480048696.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-02
Filing Date
2024-08-01
Publication Date
2026-02-17

AI Technical Summary

Technical Problem

Existing aluminum alloys exhibit decreased fatigue crack propagation resistance under variable amplitude loads as yield strength increases, making it difficult to maintain a good yield strength-toughness trade-off after low-temperature aging.

Method used

By adjusting the chemical composition of aluminum-copper-lithium alloy and employing a process flow of casting, homogenization, hot deformation, solution heat treatment, quenching, controlled stretching, and tempering, the average equivalent diameter and density of Mn dispersions and δ' precipitates were controlled, and the texture was optimized, thus producing aluminum-copper-lithium alloy plates with excellent spectral fatigue resistance and thermal stability.

Benefits of technology

After aging at 85℃ for 1000 hours, aluminum-copper-lithium alloy sheets still maintain excellent spectral fatigue resistance and yield strength-toughness trade-off, making them suitable for aerospace structural components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121548656A_ABST
    Figure CN121548656A_ABST
Patent Text Reader

Abstract

The invention relates to a rolled product made of an aluminum alloy having a thickness of 15 mm to 50 mm, consisting of, in% by weight, Cu: 2.3-2.7; 1.3 to 1.7 parts of Li; 0.2 to 0.5 part of Mg; 0.2 to 0.5 part of Mn; 0 to 0.1 part of Ag; zn: lt; 0.20, 0.20; 0.01 to 0.15 percent of Ti; zr < lt >; 0.07, 0.07; fe < lt >; 0.1 part; si < lt >; 0.1 part; other elements per lt; 0.05 and the sum lt; 0.15, the remainder being aluminum, in which phases having an equivalent diameter of 35 to 500 nm have an average equivalent diameter of less than or equal to 100 nm. The product according to the invention is obtained by a method wherein in particular the thermal deformation conditions are such that the final thermal deformation temperature is at least 400 DEG C, and the solution heat treatment of the product comprises a step from 540 DEG C to 580 DEG C for at least 15 minutes and less than 8 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention generally relates to products made of aluminum alloys, and more specifically to said products, their manufacturing methods and uses, particularly in the aerospace industry. Background Technology

[0002] In aluminum alloys, it is generally believed that the fatigue crack propagation resistance under variable amplitude loads (referred to as "fatigue under spectrum" in this application) decreases with increasing yield strength and vice versa (Rioja RJ et al. "The role of crystallographic texture on the performance of flat rolled aluminum products for aerospace applications" LIGHT METALS-WARRENDALE-PROCEEDINGS- 2008, 1065).

[0003] In Chapter 11, pages 341-375 of *Aluminum-Lithium Alloys – Processing Properties and Applications*, Elsevier, 2014, Prasad et al. mention that the improvement of fatigue resistance in lithium alloys is achieved through solution hardening and the coalescence of δ-precipitates. Furthermore, fatigue can also be improved through heat treatment and thermomechanical treatment involving tempering (also known as artificial aging) or pre-tempering cold deformation.

[0004] U.S. Patent US9234566 may be mentioned, which discloses a method for manufacturing an aluminum alloy, comprising the steps of: (i) preparing a first aluminum alloy for artificial aging; and (ii) artificially aging the first aluminum alloy. In one method, the preparation step (i) comprises: (a) solution heat treatment of an alloy containing at least 0.1 wt% Li at a temperature of at least 800℉ (426°C), and (b) quenching the alloy. The method may optionally include a step of cold deformation of the alloy. The artificial aging step (ii) comprises at least two artificial aging steps, one of which comprises (c) aging the first aluminum alloy at a temperature of at least about 250℉ (121°C), and the last step (i.e., the final artificial aging step) comprises (d) aging the first aluminum alloy at a temperature not exceeding about 225℉ (107°C) for at least about 20 hours.

[0005] US Patent 5,032,359 describes a large class of aluminum-copper-lithium alloys in which the addition of magnesium and silver, particularly in the range of 0.3 to 0.5% by weight, improves mechanical strength.

[0006] US Patent 5,198,045 describes a class of alloys comprising (by weight) (2.4–3.5%) Cu, (1.35–1.8%) Li, (0.25–0.65%) Mg, (0.25–0.65%) Ag, and (0.08–0.25%) Zr. Forged products made from these alloys exhibit a density of less than 2.64 g / cm³ and a good balance between mechanical strength and toughness.

[0007] U.S. Patent 7,229,509 discloses an alloy comprising (by weight) (2.5-5.5%) Cu, (0.1-2.5%) Li, (0.2-1.0%) Mg, (0.2-0.8%) Ag, (0.2-0.8%) Mn, and (up to 0.4%) Zr or other refining agents such as Cr, Ti, Hf, Sc, and V. The given examples offer a compromise between improved mechanical strength and fracture toughness, but have a density greater than 2.7 g / cm³. 3 .

[0008] Patent EP 1,966,402 discloses a zirconium-free alloy designed for use as fuselage skin sheet, having a substantially recrystallized structure, comprising (by weight) (2.1-2.8) Cu, (1.1-1.7) Li, (0.2-0.6) Mg, (0.1-0.8) Ag and (0.2-0.6) Mn.

[0009] Patent EP 1,891,247 discloses an alloy designed for use in fuselage skin sheets, comprising (by weight) (3.0-3.4) Cu, (0.8-1.2) Li, (0.2-0.6) Mg, (0.2-0.5) Ag, and at least one element selected from Zr, Mn, Cr, Sc, Hf, and Ti, wherein the Cu and Li contents satisfy the condition Cu + 5 / 3 Li < 5.2.

[0010] US Patent 5,455,003 discloses a method for preparing an aluminum-copper-lithium alloy that exhibits improved mechanical strength and toughness at low temperatures. This method is particularly suitable for alloys comprising (by weight) (2.0-6.5%) Cu, (0.2-2.7%) Li, (0-4.0%) Mg, (0-4.0%) Ag, and (0-3.0%) Zn.

[0011] International application WO 2010 / 055225 discloses a method for preparing a liquid metal pool comprising 2.0 to 3.5 wt% Cu, 1.4 to 1.8 wt% Li, 0.1 to 0.5 wt% Ag, 0.1 to 1.0 wt% Mg, 0.05 to 0.18 wt% Zr, 0.2 to 0.6 wt% Mn, and at least one element selected from Cr, Sc, Hf, and Ti, wherein the amount of said element—if chosen—is: 0.05 to 0.3 wt% for Cr and Sc, 0.05 to 0.5 wt% for Hf, and 0.01 to 0.15 wt% for Ti, with the balance being aluminum and unavoidable impurities; the liquid metal pool is cast into a rough shape, and said rough shape is homogenized at a temperature of 515°C to 525°C, such that the equivalent time for homogenization at 520°C is 5 to 20 hours.

[0012] International application WO2011 / 141647 relates to an aluminum-based alloy comprising (by weight) 2.1 to 2.4% Cu, 1.3 to 1.6% Li, 0.1 to 0.5% Ag, 0.2 to 0.6% Mg, 0.05 to 0.15% Zr, 0.1 to 0.5% Mn, 0.01 to 0.12% Ti, optionally at least one element selected from Cr, Sc, and Hf, wherein the amounts of the elements—if chosen—are 0.05 to 0.3% for Cr and Sc, and 0.05 to 0.5% for Hf, the amounts of Fe and Si are each less than or equal to 0.1%, and the contents of unavoidable impurities are each less than or equal to 0.05 and the sum is less than or equal to 0.15. This alloy can be used to manufacture extruded, rolled, and / or forged products, and is particularly suitable for manufacturing underwing components for aircraft.

[0013] The article "Effect of microstructure and load ratio on fatigue crack growth behavior of advanced Al-Cu-Li-Mg-Ag alloys" by Lee Chang-Soon et al., Metals and Materials, Vol 3 Issue 1 (1997) pp 51-59, describes the fatigue crack propagation behavior on three Al-Cu-Li-Mg-Ag alloys with load ratios of 0.1 and 0.75.

[0014] EP3077559 discloses a method for manufacturing rolled or forged materials with a thickness of 14 to 100 mm. The material is composed of an aluminum alloy comprising (by weight%): 1.8-2.6 Cu; 1.3-1.8 Li; 0.1-0.5 Mg; 0.1-0.5 Mn; Zr < 0.05; 0-0.5 Ag; Zn < 0.20; 0.01-0.15 Ti; Fe < 0.1; Si < 0.1; other elements each < 0.05 and their sum < 0.15; the remainder being aluminum with a density less than 2.670 g / cm³. The method comprises: homogenization; hot rolling at a final temperature of at least 400°C; preferably solution heat treatment at 490 to 530°C for 15 minutes to 8 hours; followed by water quenching, typically. Subsequently, the sheet undergoes controlled stretching of 1% to 6% and is then tempered at 120 to 170°C for 5 to 100 hours. The inventors noted that the product disclosed in EP3077559 achieves satisfactory spectral fatigue resistance, but its toughness decreases after aging at 85°C for 1000 hours or 3000 hours.

[0015] CN113718096 discloses a method for preparing high-performance aluminum-lithium alloy plates. The method includes casting, rolling, solution heat treatment, quenching, stretching, and tempering steps.

[0016] The paper "Effect of single and duplex aging on precipitation response microstructure and fatigue crack behavior in Al-Li-Cualloy AF / C-458," published by Fragomeni et al. in the *Journal of Materials Engineering and Performance*, Vol. 14, No. 1, February 2005, pp. 18-27, discloses the changes in size, distribution, morphology, volume fraction, density, and interparticle spacing of precipitates δ' and T1 under aging conditions in an aluminum-copper-lithium alloy with the composition Al-1.8 wt%, Li-2.7%, Cu-0.3%, Mg-0.5%, Zr-0.3Mn-0.8Zn (named AF / C 458). The study shows that when the δ' phase precipitate size is less than 20 nm, the fatigue crack propagation threshold increases. However, this finding contradicts other research results. For example, Rao KT Enkateswara's paper "Mechanisms of Fatigue Crack Propagation and Fracture Toughness Behavior in Advanced Aluminum-Lithium Alloys" published in 1988 can be mentioned. Page 66 shows that for AA2091 type alloys, the fatigue crack propagation threshold in the T8 state is higher than that in the T3 state, which proves that δ' phase precipitates have a positive effect in this case.

[0017] To reduce the weight of aerospace structural components, it is necessary to further improve the spectral fatigue resistance of materials, while taking into account the trade-off between yield strength and toughness, even after low-temperature aging (preferably aging at 85°C for 1000 hours).

[0018] This application aims to provide a method for obtaining a product that improves spectral fatigue resistance and yield strength-toughness trade-off even after aging at 85°C for 1000 hours. Summary of the Invention

[0019] The first objective of this invention is a method for manufacturing rolled or forged aluminum-copper-lithium alloy products. The method comprises the following steps performed sequentially:

[0020] (a) Cast alloy plate, comprising, by weight %: Cu: 2.3 – 2.7; Li: 1.3 – 1.7; Mg: 0.2 – 0.5; Mn: 0.2 – 0.5; Ag: 0 – 0.1; Zn: < 0.20; Ti: 0.01 – 0.15; Zr < 0.07; Fe < 0.1; Si < 0.1; other elements each < 0.05 and the sum < 0.15, with the balance being aluminum.

[0021] (b) Homogenize the plate at 480°C to 540°C for 5 to 60 hours.

[0022] (c) The homogeneous plate is hot-deformed by rolling to obtain an intermediate product with a thickness of 15 to 50 mm, and the final hot-deformation temperature is at least 400°C.

[0023] (d) Solution heat treatment of the intermediate product.

[0024] (e) The intermediate product that has undergone solution heat treatment is subjected to water quenching.

[0025] (f) The intermediate product after solution heat treatment and quenching is subjected to controlled stretching with a permanent deformation rate of 2 to 5%.

[0026] (g) The intermediate product that has undergone solution heat treatment, quenching and stretching is tempered by heating at 120 to 170°C for 5 to 100 hours.

[0027] The method is such that the solution heat treatment performed in step (d) includes step d1) which lasts for at least 15 minutes and less than 8 hours, during which the intermediate product is at a temperature of 540°C to 580°C.

[0028] Advantageously, the solution heat treatment performed in step d) includes step d2) 15 min to 8 h after step d1), during which the intermediate product is at a temperature of 480°C to 535°C.

[0029] Preferably, the equivalent time t_eq of the tempering at 155°C is 30 to 60 hours, or even more preferably 45 to 55 hours.

[0030] The equivalent time t_eq at 155℃ is defined by the following formula:

[0031]

[0032] Where T (in Kelvin) is the instantaneous processing temperature, which varies with time t (in hours), and Tref is a reference temperature set to 428K (155℃). t_eq is expressed in hours.

[0033] Another object of the present invention is a rolled product with a thickness of 15 mm to 50 mm, made of a lithium-copper-aluminum alloy, the composition of which, by weight percent: Cu: 2.3 – 2.7; Li: 1.3 – 1.7; Mg: 0.2 – 0.5; Mn: 0.2 – 0.5; Ag: 0 – 0.1; Zn: < 0.20; Ti: 0.01 – 0.15; Zr < 0.07; Fe < 0.1; Si < 0.1; other elements each < 0.05 and the sum < 0.15, with the balance being aluminum. This product is characterized in that the average equivalent diameter of the phase group with an equivalent diameter between 35 and 500 nm is less than or equal to 100 nm. The term "phase" refers to Mn dispersions or precipitates. Preferably, the product is characterized in that the average equivalent diameter of the Mn dispersion phase group with an equivalent diameter between 35 and 500 nm is less than or equal to 100 nm.

[0034] Advantageously, the phase density with an equivalent diameter between 35 and 500 nm is greater than or equal to 1.3 phases / µm². Preferably, the product is characterized in that the density of Mn dispersions with an equivalent diameter between 35 and 500 nm is greater than or equal to 1.3 phases / µm².

[0035] Advantageously, the area fraction of the phase with an equivalent diameter of 35 to 500 nm is less than or equal to 0.8%. Preferably, the product is characterized in that the area fraction of Mn dispersions with an equivalent diameter between 35 and 500 nm is less than or equal to 0.8%.

[0036] In another preferred embodiment, the equivalent diameter is 35 to 500 nm and is greater than or equal to 1.0%. Preferably, the product is characterized in that the area fraction of Mn dispersions with an equivalent diameter of 35 to 500 nm is greater than or equal to 1.0%.

[0037] Advantageously, the texture of the rolled product measured at the median thickness is such that the sum of the volume fractions of the Copper, Brass, and S texture components is less than or equal to 5%.

[0038] Advantageously, at the median thickness, the grain structure of the product is essentially recrystallized. Attached Figure Description

[0039] Figure 1 The yield strength versus toughness trade-off is shown under the conditions of Example 1, with or without aging treatment.

[0040] Figure 2 The relationship between the flight number under spectral fatigue and the solution heat treatment temperature is shown according to the conditions of Example 2.

[0041] Figure 3 The relationship between the flight number under spectral fatigue and the average Dcircle value of each phase, including Mn dispersions and δ' precipitates, is shown according to the conditions of Example 2.

[0042] Figure 4 The relationship between the flight number under spectral fatigue and the area of ​​the first dissolution peak measured by differential calorimetry is shown under the conditions defined in Example 2. Detailed Implementation

[0043] Unless otherwise stated, all designations of the chemical composition of the alloys are expressed as weight percentages based on the total weight of the alloy. Alloy naming conforms to the guidelines of the Aluminum Association, which are known to those skilled in the art. Density depends on the composition and is determined by calculation rather than by weighing. This value is calculated according to the Aluminum Association's guidelines, which are described on pages 2-12 and 2-13 of "Aluminum Standards and Data". The definition of the state is listed in European Standard EN 515.

[0044] Unless otherwise mentioned, static mechanical properties, i.e., ultimate tensile strength R m Tensile yield strength R p0.2 Ultimate elongation (A%) is determined according to the tensile test according to standard EN 10002-1 or NF EN ISO 6892-1. Sampling location and orientation are defined by standard EN 485-1. Unless otherwise specified, the definitions of standard EN 12258 apply.

[0045] The inventors noted that by adjusting the chemical composition, solution heat treatment conditions, and tempering conditions, they were able to improve the fly number and thermal stability of the product under spectral fatigue.

[0046] The product according to the present invention is obtained by a process including casting, homogenization, hot deformation, solution heat treatment, quenching, controlled stretching and tempering steps.

[0047] Casting of aluminum alloy plates according to the present invention.

[0048] The copper content of the alloy according to the invention is from 2.3% to 2.7% by weight. Preferably, the copper content is at least 2.4% or 2.5% by weight, more preferably at least 2.45% by weight, or more preferably at least 2.50% by weight. The maximum copper content is 2.6% by weight, or preferably 2.60% or 2.55% by weight.

[0049] The lithium content is 1.3% to 1.7% by weight. Advantageously, the lithium content is at least 1.35% by weight, preferably 1.40% by weight. Preferably, the lithium content is at most 1.65% by weight or preferably 1.60% by weight.

[0050] The silver content is 0 to 0.1% by weight. In one embodiment of the invention, the silver content is 0.01 to 0.1% by weight. In another embodiment of the invention, which has the advantage of minimizing density, the silver content is at most 0.05% by weight.

[0051] The magnesium content is between 0.2% and 0.5% by weight. Preferably, the magnesium content is at most 0.4% by weight. In an advantageous embodiment of the invention, the magnesium content is at least 0.20% by weight.

[0052] The manganese content is 0.2 to 0.5% by weight, preferably 0.20 to 0.50% by weight. Preferably, the manganese content is at least 0.25% by weight, even more preferably at least 0.30% by weight. Preferably, the manganese content is at most 0.45% by weight, even more preferably at most 0.40% by weight.

[0053] The zirconium content is less than 0.07% by weight. Preferably, the zirconium content is less than or equal to 0.05% by weight, and even more preferably less than or equal to 0.04% by weight. Preferably, the zirconium content is at least 0.01% by weight.

[0054] The alloy also contains 0.01 to 0.15% by weight of Ti, preferably 0.02 to 0.10% by weight, in order to control the grain size, especially during casting.

[0055] The zinc content is less than 0.20% by weight. Preferably, the zinc content is less than 0.05% by weight, or even 0.04% by weight.

[0056] The unavoidable impurity content in the alloy is preferably limited to achieve the most favorable damage tolerance performance. Unavoidable impurities include iron and silicon, each in a content of less than 0.1% by weight, or even less than 0.08% by weight. Preferably, the content of iron and silicon is less than 0.06% by weight each. The content of other impurities is less than 0.05% by weight each, and the sum is less than 0.15% by weight. The balance corresponds to aluminum.

[0057] The cast plate is then homogenized. Homogenization is carried out at a temperature of 480°C to 540°C for 5 to 60 hours. Preferably, the homogenization temperature is 490°C to 510°C.

[0058] After homogenization, the sheet is typically cooled to ambient temperature and then preheated for hot deformation by rolling. The purpose of preheating is to reach the initial deformation temperature, preferably 420 to 520°C, more preferably about 450 to 480°C, so that the sheet can be deformed.

[0059] Hot deformation is carried out by hot rolling to obtain plates with a thickness between 15 mm and 50 mm. The hot rolling conditions are selected such that the final hot deformation temperature is at least 400°C, preferably at least 405°C, or even 410°C.

[0060] Several technical solutions exist for achieving this temperature at the hot rolling exit. One approach is to use a reheating chamber and / or a cooling chamber to achieve an exit temperature of at least 400°C. Heated rolls can also be used. The number of rolling passes, deformation rate, and rolling speed can also be adjusted.

[0061] The rolled sheet is then subjected to solution heat treatment. The inventors noted that, in order to improve the flight number under spectral fatigue while maintaining an excellent trade-off between R0.2 – L and Kapp TL, and to achieve excellent thermal stability, it is important to perform a solution heat treatment, including step d1), at a temperature of 540°C to 580°C for at least 15 minutes and less than 8 hours. Preferably, the solution heat treatment temperature is at least 550°C.

[0062] According to a preferred embodiment, the solution heat treatment step may include several steps. According to a preferred embodiment of the invention, it is advantageous to perform step d2) at a temperature of 480°C to 535°C, preferably 480°C to 530°C, at the end of step d1). Preferably, the duration of step d2) is from 15 minutes to 8 hours. The inventors have noted that performing solution heat treatment at 540°C to 580°C for step d1) and then at 480°C to 535°C for step d2) can improve the elongation of the product in the LT direction and its machinability.

[0063] According to another preferred manufacturing method, it may be advantageous not to perform the second step d2) after step d1). The inventors have noted that this approach can achieve a longer spectral fatigue life.

[0064] The plate is then quenched in water, usually at room temperature, preferably below 40°C.

[0065] The product is then subjected to controlled stretching of 2% to 5%, preferably at least 3%, and typically about 4%.

[0066] The product is then tempered at 120 to 170°C for 5 to 100 hours, preferably at 140 to 160°C for 30 to 90 hours. Preferably, the tempering results in an equivalent time t_eq of 30 to 60 hours at 155°C. More preferably, the equivalent time t_eq at 155°C is at least 32, 34, or 36 hours. To improve the product's elongation in the LT direction and machinability, an equivalent time t_eq of 30 to 40 hours at 155°C may be advantageous. In another preferred embodiment, the equivalent time t_eq at 155°C is 45 to 55 hours to improve the product's thermal stability.

[0067] The equivalent time t_eq at 155℃ is defined as follows:

[0068]

[0069] Where T (in Kelvin) is the instantaneous processing temperature of the metal, which varies with time t (in hours). ref The reference temperature is set at 428 K (155 °C). t_eq is expressed in hours. The constant Q / R = 11400 K originates from the lithium diffusion activation energy Q = 95000 J / mol. The formula for calculating t_eq takes into account both heating and cooling phases.

[0070] For sheet metal, the preferred metallurgical state is T8, especially T84 or T86.

[0071] The inventors noted that the product obtained by the method described in this invention exhibits excellent spectral fatigue resistance and good thermal stability after aging at 85°C for 1000 hours. Since the obtained material is intended for use in the aerospace field, an aging test was conducted at 85°C for 1000 hours to simulate the material's operational performance process.

[0072] The inventors attribute this superior performance to the microstructure of the product achievable through the aforementioned process. Not wanting to be bound by theory, the inventors believe that an average equivalent diameter of phases smaller than 100 nanometers can improve spectral fatigue and thermal stability.

[0073] In this invention, "phase" refers to Mn dispersions and / or precipitates. The phase groups considered according to the invention have an equivalent diameter between 35 nm and 500 nm. It should be understood that each considered phase has an equivalent diameter between 35 nm and 500 nm. Primary intermetallic compounds formed during casting are excluded. They differ from the phases considered in this invention in that their size is significantly larger than 500 nm. The Mn dispersions contain aluminum and manganese, and optionally at least one element selected from iron, copper, and silicon. The Mn dispersions can be Al-Mn, Al-Mn-Fe, Al-Mn-Cu-Fe, or Al-Mn-Fe-Si type compounds. The Mn dispersions are formed during homogenization. For example, Al 15 (Mn,Fe)3Si2 can be considered a dispersion. The precipitate contains a combination of Al, Cu, and Li elements. For example, Al3Li, also known as the δ' phase, can be considered a precipitate. The precipitate forms during tempering. Preferably, the precipitate according to the present invention is an Al3Li precipitate, also known as the δ primary phase (δ').

[0074] According to the present invention, the average equivalent diameter of the phase with an equivalent diameter in the range of 35 nm to 500 nm is less than or equal to 100 nm, preferably 90 nm. Preferably, the average equivalent diameter of the phase is at least 40 nm. More preferably, the average equivalent diameter of the Mn dispersions with an equivalent diameter in the range of 35 nm to 500 nm is also less than or equal to 100 nm, preferably 90 nm. Although it is known that the presence of δ'(Al3Li) precipitates is beneficial to spectral fatigue, the inventors have noted that reducing the equivalent diameter of Mn dispersions and / or precipitates is beneficial to spectral fatigue.

[0075] Preferably, the phase density with an equivalent diameter in the range of 35 nm to 500 nm is greater than or equal to 1.3 phases / µm², more preferably greater than or equal to 1.40 phases / µm². Phase density corresponds to the number of phases per unit area. Preferably, the density of Mn dispersions with an equivalent diameter in the range of 35 nm to 500 nm is at least 1.3 Mn dispersions / µm², more preferably at least 1.40 Mn dispersions / µm². The inventors note that, to improve spectral fatigue, it is preferable to associate phases with an average equivalent diameter less than or equal to 100 nm and a phase density greater than or equal to 1.3 phases / µm².

[0076] The density, area fraction, and average equivalent diameter (also known as the average Dcircle value) of a phase can be determined using high-resolution techniques such as transmission electron microscopy (TEM) or scanning electron microscopy (SEM). These techniques can be combined with the chemical identification of the phase using techniques such as energy-dispersive X-ray spectroscopy (EDX). Image analysis is preferred for automated processing that directly tracks phase distribution. SEM observations combined with image analysis provide a good method for reporting phase density, the average equivalent diameter (average Dcircle value), and its area fraction. Only phases with an equivalent diameter between 35 nm and 500 nm are quantified. This threshold is set without considering intermetallic compounds larger than 500 nm formed during casting, or fine phases that do not provide sufficient resolution and would affect the analytical results. Results are preferably based on at least 200 images taken at high magnification (typically greater than 20,000 X, preferably greater than 30,000 X), covering a total analytical area of ​​at least 2000 µm². This covers a large portion of the product while avoiding the drawbacks of processing large amounts of data.

[0077] Phase density corresponds to the ratio of the total number of phases identified through image analysis (e.g., by setting grayscale thresholds to distinguish between the aluminum matrix and the phases) to the total area analyzed.

[0078] The equivalent diameter of a phase, or Dcircle value, corresponds to the equivalent diameter of a phase having a circular cross-section and a surface area equal to that of the observed phase (if the latter has a more complex cross-section than a simple circle). The average Dcircle value or average equivalent diameter of a phase corresponds to the average equivalent diameter of a circle with an area equal to the average area of ​​all phases.

[0079] The area fraction of a phase can also be determined using image analysis. It corresponds to the ratio of the total area covered by each phase to the total area analyzed.

[0080] According to one operating method, it is advantageous for the area fraction of the phase with an equivalent diameter of 35 nm to 500 nm to be less than or equal to 0.8%, preferably less than or equal to 0.7%. This microstructure can be obtained through solution heat treatment excluding a second step (d2) at 480°C to 535°C. This microstructure is beneficial for improving spectral fatigue.

[0081] According to another operating method, it is advantageous for the area fraction of the phase with an equivalent diameter of 35 nm to 500 nm to be greater than or equal to 1.0%, preferably 1.1%. This microstructure can be obtained through solution heat treatment including a second step (d2) at 480°C to 535°C for 15 minutes to 8 hours. This microstructure is beneficial for improving elongation in the LT direction.

[0082] Crystal texture can be described by a three-dimensional mathematical function. This function is known in the field as the orientation distribution function (ODF). It is defined as the volume fraction dV / V of the material with orientations ranging from g to dg:

[0083]

[0084] Where (φ1, Φ, φ2) are the Euler angles describing orientation g.

[0085] The inventors used the spherical harmonic method to calculate the ODF of each plate from the quadrupole diagram measured by X-ray diffraction or EBSD on a conventional texture goniometer.

[0086] The inventors used a 15° tolerance around the “copper,” “brass,” and “S” orientations to describe the obtained texture. The “copper,” “brass,” and “S” crystal orientations are known to those skilled in the art and are described, for example, in reference UF Kocks, CN Tomé and H.-R. Wenk, "Texture and anisotropy: preferred orientations in polycrystals and their effect on materials properties". Cambridge University Press, 2000.

[0087] The “copper”, “brass” and “S” orientations are shown in the table below.

[0088]

[0089] The inventors noted that if the sum of the volume fractions of the copper, brass, and S texture components measured at the median thickness of the plate is less than or equal to 5%, the product exhibits better spectral fatigue behavior.

[0090] Preferably, the product has a substantially recrystallized structure at its median thickness. A substantially recrystallized structure means a structure having at least 80%, preferably at least 90%, of recrystallized grains.

[0091] Example

[0092] Example 1

[0093] Seven compositions were cast in sheet form (Table 1). All alloys have the composition according to the invention.

[0094] [Table 1] - Chemical composition (wt%)

[0095]

[0096] All plates are homogenized, then heated, then hot rolled (HR), then melted, then quenched, then stretched, and then tempered. Manufacturing conditions and references for the corresponding thickness plates are detailed in Table 2.

[0097] [Table 2] - Manufacturing Conditions

[0098]

[0099] A-1, A-2, and B-1 are thick plates produced according to the present invention. Plate C-2 is a reference plate mentioned in patent EP3077559 (number 3A in EP3077559).

[0100] The static mechanical properties of the sheet at the median thickness (t / 2) in the L direction were measured, and the toughness at the median thickness (t / 2) in the LT direction was measured on a test piece with a width of 406 mm and a thickness of B = 6.35 mm.

[0101] Furthermore, spectral fatigue performance was tested on CCT-type test pieces with a thickness of 12 mm, a length of 700 mm, a width of 200 mm, and a 30 mm notch. This spectral fatigue performance represents the underwing conditions of commercial aircraft and meets the specifications of the aircraft manufacturer. The samples characterizing spectral fatigue were taken such that the stress direction was in the LT direction and at the center 11 mm below the surface of the sheet. Spectral fatigue results were obtained after fatigue pre-cracking until the crack reached 40 mm. The results obtained are the number of flights between 50 mm and 130 mm of crack propagation.

[0102] The tensile yield strength and toughness were also characterized after aging at 85℃ for 1000 h to evaluate thermal stability. Only some plates were tested.

[0103] [Table 3] - Mechanical Properties

[0104]

[0105] Compared to the control sheet, the A-1, A-2, and B-1 sheets produced according to the invention allow for a higher flight number under spectral fatigue. Notably, the sheet produced according to the invention exhibits an improved yield strength-toughness tradeoff after aging at 85°C for 1000 hours, while the control product shows a decrease in toughness after aging. Figure 1 ).

[0106] [Table 4] - Effects of heat exposure at 85°C for 1000 hours

[0107]

[0108] Texture measurements were performed at the median thickness of plates A-1, A-2, B-1, C-2, and G-1 using X-ray diffraction. The analyzed area was approximately 50 x 50 mm². Texture measurements for plates D-2, E-2, and F-2 were performed using EBSD. The texture results obtained using these two techniques are equivalent. Table 5 shows the % volume fraction of brass, copper, and S orientation for each sample.

[0109] [Table 5] - Results of texture measurements (volume fraction %)

[0110]

[0111] The plates A-1, A-2, and B-1 produced according to the present invention are 100% recrystallized at their median thickness. The sum of the volume fractions of Copper + Brass + S is less than 5%. Plates A-1 and A-2 have the same texture. The texture is not affected by aging conditions.

[0112] Example 2

[0113] According to the conditions of the present invention, a 24 mm thick sheet of composition H (Table 6) is rolled. The rolled sheet is then cut and subjected to solution heat treatment, quenching, stretching, and tempering under different conditions. The transformation conditions are shown in Table 7 below.

[0114] [Table 6] – Chemical Composition (wt%)

[0115]

[0116] [Table 7] – Conversion Conditions

[0117]

[0118] All sheet metal samples underwent tensile testing in the LT and TL directions, as well as spectral fatigue testing, at median thickness. Spectral fatigue represents underwing conditions for commercial aircraft conforming to aircraft manufacturer specifications, targeting CCT-type test pieces with a thickness of 12 mm, a length of 700 mm, a width of 200 mm, and a 30 mm notch. This is the same as the spectral fatigue test shown in Example 1. Samples for spectral fatigue testing were taken at median thickness of the sheet metal. Spectral fatigue results were obtained after fatigue pre-cracking until the crack reached 40 mm. The results obtained are the number of flights between 50 mm and 130 mm crack propagation. The results are shown in Table 8.

[0119] Table 8

[0120]

[0121] These identical plates were characterized by scanning electron microscopy to quantify phase distribution. Microstructure characterization was performed on the L-TC plane to observe the median thickness of the plates. Quantization yielded approximately 200 images with dimensions of 5 x 3.75 µm, for a total analyzed area of ​​3750 µm². Only phases with equivalent diameters ranging from 35 nm to 500 nm were considered. This allowed for the omission of large intermetallic compounds that might be associated with casting.

[0122] Phase density is the ratio of the total number of phases identified through image analysis (e.g., distinguishing between the aluminum matrix and phases by setting grayscale thresholds) to the total area analyzed. The average area fraction of a phase, Fs, is the ratio of the total area of ​​the analyzed phase to the analyzed surface area. The average equivalent diameter of a phase corresponds to the average Dcircle value. The average Dcircle value corresponds to the equivalent diameter of a circle with a surface area equal to the average surface area of ​​the analyzed phase.

[0123] Phases were observed in all samples. It was observed that the phases in the samples of this invention were small in size, with an average Dcircle value of less than 100 nm. Morphological parameters of the analyzed phases are shown in Table 9. The phase quantification shown in Table 9 considers phases with sizes ranging from 35 nm to 500 nm, without distinguishing whether the phase is a Mn dispersion or a δ' precipitate.

[0124] [Table 9]

[0125]

[0126] Note the correlation between the flight number under spectral fatigue and the solution heat treatment temperature. Figure 2 The inventors noted that the improvement in spectral fatigue was negatively correlated with the average Dcircle value. Figure 3 Similarly, a good correlation was achieved with phase density.

[0127] Sample H60-bi corresponds to the following solution heat treatment according to the invention, namely, first performing step d1) from 540°C to 580°C, followed by step d2) from 480°C to 535°C. In this case, it can be noted that the second step d2) tends to increase the area fraction of the phase to more than 1.0%, while maintaining the average equivalent diameter of the phase less than 100 nm and / or the density greater than or equal to 1.3 phase / µm². The average area fraction of samples H-40, H-60, and H-75 undergoing a single step d1) from 540°C to 580°C according to the invention is less than or equal to 0.8%. The average area fraction of sample H60-bi undergoing step d1) from 540°C to 580°C followed by step d2) from 480°C to 535°C according to the invention is greater than or equal to 1.0%.

[0128] The inventors noted that this microstructure not only maintains good spectral fatigue performance but also improves elongation in the LT direction. Indeed, it has been observed that tensile yield strength and ultimate stress are less affected by solution heat treatment temperature; however, elongation in the LT direction decreases with solution heat treatment temperature. Nevertheless, solution heat treatment involving two steps (d1) and d2) appears to improve elongation in the LT direction.

[0129] In the second phase, the inventors independently analyzed the Mn dispersions and δ' precipitates. The presence of δ' precipitates was observed in all samples. Only samples H-00 and H-60 ​​Bi contained Mn dispersions with a size greater than 35 nm. Data processing was performed on these two samples to determine the average Dcircle values ​​of the Mn dispersions and δ' precipitates (see Table 10).

[0130] [Table 10]

[0131]

[0132] The inventors noted that, compared to the product of this invention, the product that does not conform to this invention contains a large amount of Mn dispersions with an average Dcircle value exceeding 100 nm.

[0133] Differential scanning calorimetry (DSC) was performed on the products to quantify the amount of δ' precipitate. The test method consisted of heating each product from ambient temperature to approximately 620°C at a rate of 20°C / min and recording the differential signal change with temperature.

[0134] The first dissolution peak was recorded at approximately 90°C, representing the amount of δ' precipitate present. The proportion of δ' precipitate can be quantified by the area of ​​this dissolution peak (expressed in J / g). The larger the area value, the greater the amount of δ' precipitate.

[0135] [Table 11]

[0136]

[0137] It has been noted that spectral fatigue resistance is independent of the amount of δ' precipitate (Table 11 and...). Figure 4 Therefore, the inventors believe that the observed improvement in spectral fatigue due to solution heat treatment temperature is mainly affected by Mn dispersions, and preferably the average Dcircle value of the Mn dispersions is less than 100 nm.

Claims

1. A method of manufacturing a rolled or forged product of an aluminum-copper-lithium alloy, wherein: (a) a cast alloy plate having a composition, in weight %: Cu: 2.3 - 2.7 Li: 1.3 - 1.7 Mg: 0.2 - 0.5 Mn: 0.2 - 0.5 Ag: 0 - 0.1 Zn: < 0.20 Ti: 0.01 - 0.15 Fe < 0.1 Si < 0.1 other elements each < 0.05 and in total < 0.15, the remainder being aluminum, (b) the plate is homogenized at 480°C to 540°C for 5 to 60 hours, (c) the homogenized plate is hot deformed by rolling to obtain an intermediate product having a thickness in the range of 15 to 50 mm, the final hot deformation temperature being at least 400°C, (d) the intermediate product is solution heat treated, (e) the solution heat treated intermediate product is quenched in water, (f) the solution heat treated and quenched intermediate product is subjected to a controlled stretching with a permanent deformation rate of 2 to 5%, (g) the solution heat treated, quenched and stretched intermediate product is tempered by heating at 120 to 170°C for 5 to 100 hours, Zr < 0.07 characterized in that the solution heat treatment in step (d) comprises a step dl) of at least 15 minutes and less than 8 hours, during which the intermediate product is at a temperature of 540°C to 580°C.

2. The manufacturing method according to claim 1, wherein the solution heat treatment performed in step d) comprises a step d2) of 15 minutes to 8 hours after step dl), during which the intermediate product is at a temperature of 480°C to 535°C.

3. The manufacturing method according to claim 1 or 2, wherein the tempering has an equivalent time t eq at 155°C of 30 to 60 hours, the equivalent time t eq at 155°C being defined by the following formula: t eq = t ref exp - (T ref - T) / 55 where T (in Kelvin) is the instantaneous treatment temperature of the metal as a function of time t (in hours), T ref is a reference temperature set at 428 K, t eq being expressed in hours.

4. The manufacturing method according to claim 3, wherein the equivalent time t eq at 155°C is 45 to 55 hours.

5. A rolled product of an aluminum-copper-lithium alloy having a thickness of 15 mm to 50 mm, having a composition, in weight %: Cu: 2.3 - 2.7 Li: 1.3 - 1.7 Mg: 0.2 - 0.5 Mn: 0.2 - 0.5 Ag: 0 - 0.1 Zn: < 0.20 Ti: 0.01 - 0.15 Fe < 0.1 Si < 0.1 other elements each < 0.05 and in total < 0.15, the remainder being aluminum, an average equivalent diameter of a population of phases having an equivalent diameter of 35 to 500 nm being less than or equal to 100 nm, wherein the phases are Mn dispersoids or precipitates, and wherein the measurement is made by SEM, based on at least 200 images covering a total analysis area of at least 2000 pm2. ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ ​ Zr < 0.07 ​ ​ ​ characterized in that ​ 6. The rolled product according to claim 5, characterized in that The density of phases having an equivalent diameter of 35 to 500 nm is greater than or equal to 1.3 phases per pm2.

7. The rolled product according to claim 5 or 6, characterized in that The area fraction of phases having an equivalent diameter of 35 to 500 nm is less than or equal to 0.8%.

8. The rolled product according to claim 5 or 6, characterized in that The area fraction of phases having an equivalent diameter of 35 to 500 nm is greater than or equal to 1.0%.

9. The rolled product according to any one of claims 5 to 8, characterized in that The sum of the volume fractions of copper, brass and S texture components measured at the median thickness is less than or equal to 5%.

10. The rolled product according to any one of claims 5 to 9, characterized in that At the median thickness, the grain structure of the product is substantially recrystallized, such that the product has at least 80% recrystallized grains.

Citation Information

Patent Citations

  • High-strength aluminum-copper-lithium sheet metal for aircraft fuselages

    EP1891247A1

  • Sheet made of high-toughness aluminium alloy containing copper and lithium for an aircraft fuselage

    EP1966402A1

  • Aluminum / copper / lithium alloy material for underwing element having enhanced properties

    EP3077559A2

  • Ultra high strength weldable aluminum-lithium alloys

    US5032359A

  • Low density high strength Al-Li alloy

    US5198045A